Characterization and Modelling of Flexible VO2 Mott Memristor for the Artificial Spiking Warm Receptor. Issue 19 (7th June 2022) - Han, Chuan Yu; Han, Zheng Rong; Fang, Sheng Li; Fan, Shi Quan; Yin, Jun Qing; Liu, Wei Hua; Li, Xin; Yang, Shi Qiang; Zhang, Guo He; Wang, Xiao Li; Geng, Li
Abstract: In this work, high‐performance VO2 Mott memristors with the simple via‐hole structure of Pt/VO2 /Pt are fabricated on flexible Kapton polymide (PI) substrate with high endurance (> 10 4 sweep‐voltage cycles), good bending stability (> 10 3 ), and low operating current (< 130 µ A). The electrical properties of flexible memristor are well modeled by using the 3D Poole–Frenkel emission and Newton's law of cooling considering the temperature dependence of electrical and thermal properties of VO2 . As a result, a flexible artificial spiking warm receptor is achieved by using a single VO2 Mott memristor driven by a current source. And an oscillation circuit model is presented to thoroughly study the effects of the memristor electrical properties on the spiking frequency. With the stimulus temperature elevated from 20 to 40 ° C, the spiking frequency of artificial spiking warm receptor first increases, then falls off rather quickly to zero at the higher temperature of 45 ° C, resembling the response characteristics of biological warm receptors. Hence, the proposed flexible artificial spiking warm receptor is a promising candidate for the bio‐inspired electronic skin of spike‐based intelligence machines with neuromorphic computing. Abstract : The flexible VO2 Mott memristor with high performance is fabricated, characterized, and modeled. Based on a single Mott memristor, the artificial spiking warm receptor resembling the response characteristics of biological warm receptors is realized driven by a current source.